2018
DOI: 10.1055/a-0638-8295
|View full text |Cite
|
Sign up to set email alerts
|

Video Tutorials Increase Precision in Minimally Invasive Surgery Training – a Prospective Randomised Trial and Follow-up Study

Abstract: Standardised comprehensive video tutorials watched frequently throughout practice can significantly improve precision in MIC training. This aspect should be incorporated in MIS training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
1
2
0
1
Order By: Relevance
“…The third test (T3) was unnecessary since all the participants were able to perform the technique by the end of T2, although some took longer than the time stipulated. This observation of the effect of tutorial videos on learning was already noted in other studies 10,11. In laparoscopic surgery, Stefanidis and colleagues concluded that video tutorials can accelerate learning and improve resource utilization by minimizing the need for instructor participation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The third test (T3) was unnecessary since all the participants were able to perform the technique by the end of T2, although some took longer than the time stipulated. This observation of the effect of tutorial videos on learning was already noted in other studies 10,11. In laparoscopic surgery, Stefanidis and colleagues concluded that video tutorials can accelerate learning and improve resource utilization by minimizing the need for instructor participation.…”
Section: Discussionsupporting
confidence: 70%
“…This observation of the effect of tutorial videos on learning was already noted in other studies. 10,11 In laparoscopic surgery, Stefanidis and colleagues concluded that video tutorials can accelerate learning and improve resource utilization by minimizing the need for instructor participation.…”
Section: Discussionmentioning
confidence: 99%
“…As an important element, the RoSTraC cloud includes video tutorials that teach the theoretical and practical basics of RAS to the trainee. Indeed, previous studies showed that video tutorials can partially replace direct in-person instruction and feedback [ 15 17 ]. Furthermore, the RoSTraC is designed to provide surgical training in the trainee’s own clinic using the in-house robotic system.…”
Section: Discussionmentioning
confidence: 99%
“…Der wichtigste Schritt zur Verbesserung der Lernkurve sind nach unserer Auffassung strukturierte und spezielle Schulungsprogramme, die insbesondere in der komplexen roboterassistierten Pankreaschirurgie einen festen Stellenwert haben müssen. Strukturierte Video-Tutorials könnten hier, wie auch in der laparoskopischen Chirurgie, die chirurgischen Fähigkeiten im OP verbessern, auch wenn sie nicht verfahrensspezifisch sind [27]. Zur Einübung eines operativen Eingriffs können Schulungsprogramme und eine Vereinheitlichung von Operationsschlüsselschritten dienen.…”
Section: Aufbau Der Robotisch Assistierten Pankreaschirurgieunclassified